Tinjauan Permohonan Kasasi Penuntut Umum Terhadap Putusan Bebas Dalam Perkara Illegal Fishing - Prata Aditya Putra; Sri Wahyuningsih Yulianti, S,H., M.H (Sebelas Maret University, 2019)
This research aims to know the reason of Cassation by the Prosecutor in fulflment of the provisions of article 253 KUHAP. This research is a normative, legal research with the criminal offence of illegal fshing case, catching fsh and operating fshing vessels without offcial documents by defendant Elmer Luas aka Elmer as the Captain of Motor Ship (KM) Anthonius-01. Based on the results of research and discussion, the Public Prosecutor were able to prove the suitability of the reasons of Cassation granted by reasons of Cassation contained in article 253 paragraph (1) of the KUHAP, especially on the letter a. The reasons for the appeal which has been described by the Public Prosecutor in those illegal fshing case can be seen where the Judex Factie misapplied the law, in case of not considering the statement of the Expert and Letter of Evidence so that the Panel of Judges imposing a free verdict against the Defendant.Keywords: Cassation, Prosecutor, Illegal Fishing